Combining manure with mineral N fertilizer maintains maize yields: evidence from four long-term experiments in Kenya - Laub, M.; Corbeels, Marc; Ndungu, S.M.; Mucheru-Muna, M.; Mugendi, D.; Necpalova, M.; Broek, M. van de; Waswa, W.; Vanlauwe, Bernard; Six, Johan (Elsevier, 2023)
Context Crop productivity in sub-Saharan Africa cannot be substantially improved without simultaneously addressing short-term crop nutrient demand and long-term soil fertility. Integrated soil fertility management tackles both by the combined application of mineral fertilizers and organic resource inputs but few studies examined its‘ long-term effectiveness.